Entrepreneurial Spirit and Product Innovation in Enhancing Business Success of Snack Food MSMEs: The Role of Business Motivation - Erni Yuningsih; Endang Silaningsih; Siti Halimatussadiah (BALANCE: Economic, Business, Management and Accounting Journal, 2026)
This analysis examines the influence of entrepreneurial spirit and product innovation on business success driven by entrepreneurial motivation. This research method uses a quantitative approach with a purposive sampling technique involving 40 respondents. This study uses a descriptive and verification approach, with a focus on quantitative data. Data were collected through questionnaires using a non-probability sampling method. The stages of this analysis include descriptive verification, validity and reliability tests, multiple linear regression, and path analysis. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) program. The results of the study are: Entrepreneurial spirit and product innovation have a direct and positive influence on entrepreneurial motivation. Entrepreneurial spirit and motivation have a direct, positive impact on business success. Meanwhile, product innovation does not have a direct and positive influence on business success. Entrepreneurial spirit and product innovation indirectly and positively influence business success through entrepreneurial motivation